From the rivers of Babylon to the highlands of Judah : collected studies on the Restoration period - Japhet, Sara (Eisenbrauns, 2006)
Culled from various books, journals, and festscrifts, the most important essays by Sara Japhet on the biblical restoration period and the books of Ezra-Nehemiah and Chronicles appear in this accessible collection. Japhet, who is Yehezkel Kaufmann Professor of Bible at the Hebrew University of Jerusalem and received the Israel Prize for biblical scholarship in 2004, has been a leading scholar on these topics for more than 30 years. Included here are studies on the question of common authorship of Ezra-Nehemiah and Chronicles, the temple during the restoration period, the use of the law in Ezra-Nehemiah, postexilic historiography, the "remnant" and self-definition during the restoration period, the historical reliability of Chronicles, and conquest and settlement in Chronicles. Scholars and students with an interest in the history, historiography, and theology of the restoration period, and in the interpretation of Ezra-Nehemiah and Chronicles will want to own this compendium of valuable essays.